Industrial entrepreneur's perception of greenhouse gas emission and its impact in Vientiane Capital, Lao PDR - Bounmy Inthakesone; Khampheng Kingkhambang; Pakaiphone Syphoxay; Phouthone Singhalath; Salika Phavongxay; Syvanh Phonasa (Annals of Environmental Science and Toxicology - Peertechz Publications, 2023)
Laos ranked 8th in terms of total greenhouse gas emissions among ASEAN countries, with 17.9 million metric tons of carbon dioxide equivalent (MtCO2e) emissions. The energy sector was responsible for the majority of emissions, accounting for about 50% or 8.9 MtCO2e, followed by the agriculture sector at around 35% or 6.3 MtCO2e, and other sectors at approximately 15% or 2.7 MtCO2e (The Global Carbon Atlas reported, 2018). This study investigates greenhouse gas emissions and environmental issues among industrial entrepreneurs in Vientiane Capital, Lao PDR. Data was collected by using questionnaires and face-to-face interviews were conducted with participants from 80 different plants in Vientiane Capital between January 25 and March 20, 2018. It identifies various environmental problems caused by industrial plants, emphasizing the need for specific pollution source mitigation and sustainable waste management. The study reveals significant impacts on health and living conditions, highlighting the urgency for proactive measures. Climate variations, alterations in seasons, and intensified storms are identified as major contributors to violence levels. Strategies proposed by entrepreneurs include accurate measurement methods, pollution treatment systems, improved power efficiency, renewable energy adoption, an environmental protection organization, and efficiency enhancements in logistics and transportation. The study emphasizes the role of government, plant owners, and the general population in addressing CO2 emissions through collective efforts. Overall, it provides valuable insights and calls for proactive measures, stakeholder engagement, and diverse strategies for sustainability in Vientiane Capital and Laos.